ANALYSIS OF THE HEAVY METAL CONTENT OF LEAD AND MERCURY IN FRESHWATER SEA SHELLS IN THE RIVER KRUENG SABEE ACEH JAYA - Wahyuni, Srie; Yanti, Nova; Idroes, Ghazi Mauer (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2023)
Gold mining in Aceh Jaya, specifically in Gunong Ujeun, results in the discharge of waste water containing heavy metals into nearby rivers. This can negatively impact the environment, particularly through contamination by lead and mercury. These heavy metals can be toxic to aquatic life, potentially disrupting the food chain. Kijing clams, a type of shellfish commonly found in freshwater rivers, are particularly susceptible to metal accumulation due to their filter feeding behavior. This research aims to assess the impact of lead and mercury levels in the Krueng Sabe river on the accumulation of these metals in shellfish, exceeding the threshold set for the river in Aceh Jaya Regency. The study will use Atomic Absorption spectroscopy (AAS) to measure the heavy metal content. The results show that the lead content in shellfish meat is 0.191 mg/kg, while the mercury content is 0.255 mg/kg. These levels are below the maximum limits set for heavy metals in food.